Qur'anic Interpretation and the Formation of Wasatiyyah Discourse in Contemporary Indonesia - Fakhrie Hanief; Anwar Hafidzi (STIT Syekh Muhammad Nafis Tabalong, 2026)
The increasing religious polarization in Indonesia has triggered urgent debates about how moderate Islamic identity can be maintained in a diverse society. Within this context, the concept of wasatiyyah (moderation) has become a central theological and policy framework, yet most existing scholarship treats it as a static doctrinal category rather than a dynamically constructed discourse. This study addresses this gap by examining how Qur'anic interpretation actively shapes the formation of wasatiyyah discourse in contemporary Indonesia. The research aims to analyze the interpretive mechanisms through which Qur'anic verses related to moderation are mobilized by Indonesian scholars and religious institutions to construct inclusive religious narratives aligned with national policy agendas. Employing a qualitative methodology that integrates textual analysis of key Qur'anic verses (including ummatan wasatan, anti-ghuluw, and justice-related passages) with discourse analysis of interpretive frameworks from major Indonesian religious institutions, this study reveals three principal findings: first, wasatiyyah emerges as a polysemic concept negotiated through diverse interpretive strategies emphasizing balance, justice, tolerance, and social harmony; second, contemporary Indonesian tafsir increasingly adopts maqasid-oriented and contextual approaches that transform wasatiyyah from theological principle into policy-relevant discourse; and third, institutional actors such as Nahdlatul Ulama, Muhammadiyah, and the Ministry of Religious Affairs play decisive roles in mediating interpretive authority. The study concludes that understanding wasatiyyah as a discursive construct rather than fixed doctrine offers more productive pathways for strengthening religious moderation initiatives, and recommends greater attention to interpretive pluralism and contextual hermeneutics in moderation policy frameworks.